2022
DOI: 10.3390/ijms23136943
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Strong Transversal s(TE) Exciton–Polaritons in C60 Thin Crystalline Films

Abstract: If an exciton and a photon can change each other’s properties, indicating that the regime of their strong bond is achieved, it usually happens in standard microcavity devices, where the large overlap between the ’confined’ cavity photons and the 2D excitons enable the hybridization and the band gap opening in the parabolic photonic branch (as clear evidence of the strong exciton–photon coupling). Here, we show that the strong light–matter coupling can occur beyond the microcavity device setup, i.e., between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…On the other hand, the interaction between photons and polarization modes can result in the formation of hybrid photon polarization modes, called polaritons. The same authors [ 19 ] have shown that 2D layered nanomaterials enable the formation of well-defined exciton–polaritons even at room temperature and that the exciton–photon coupling can be manipulated simply by changing the number of single layers. These nanostructures can be applied in photonic devices, such as LED, telecommunications, or chemical and biological sensing.…”
mentioning
confidence: 99%
“…On the other hand, the interaction between photons and polarization modes can result in the formation of hybrid photon polarization modes, called polaritons. The same authors [ 19 ] have shown that 2D layered nanomaterials enable the formation of well-defined exciton–polaritons even at room temperature and that the exciton–photon coupling can be manipulated simply by changing the number of single layers. These nanostructures can be applied in photonic devices, such as LED, telecommunications, or chemical and biological sensing.…”
mentioning
confidence: 99%